2013
DOI: 10.1007/s10682-013-9636-0
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for differential survival or predation between sympatric color morphs of an aposematic poison frog

Abstract: Because variation in warning signals slows down the predator education process, aposematic theory predicts that animal warning signals should be monomorphic. Yet, warning color polytypisms are not uncommon in aposematic species. In cases where warning signal variants are separated geographically, adaptation to local predators could explain this variation. However, this cannot explain the persistence of sympatric polymorphisms in aposematic taxa. The strawberry poison frog (Oophaga pumilio) exhibits both allopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
0
40
1
Order By: Relevance
“…However, not all studies conducted on poison frogs have found evidence for positive FDS. Two recent studies of predation on polytypic and polymorphic populations of Oophaga pumilio did not find evidence that positive FDS was involved in maintaining color differences in two populations (Hegna et al 2013b, Richards-Zawacki et al 2013). However, additional investigation would be needed across the geographic distribution of Oophaga pumilio where nearly 20 polytypic morphs occur to fully understand if positive FDS maintains differences in some locations (Hegna et al 2013b).…”
Section: Frequency-dependent Selectionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, not all studies conducted on poison frogs have found evidence for positive FDS. Two recent studies of predation on polytypic and polymorphic populations of Oophaga pumilio did not find evidence that positive FDS was involved in maintaining color differences in two populations (Hegna et al 2013b, Richards-Zawacki et al 2013). However, additional investigation would be needed across the geographic distribution of Oophaga pumilio where nearly 20 polytypic morphs occur to fully understand if positive FDS maintains differences in some locations (Hegna et al 2013b).…”
Section: Frequency-dependent Selectionmentioning
confidence: 93%
“…My work in concert with that of Nokelainen (2013) raises the question whether greater predator generalization might permit increased warning signal variation in northern areas, but much additional behavioral work is needed to probe the question. At the same time, recent evidence in some poison frog systems (Richards-Zawacki et al 2013, Amézquita et al 2013) and from examining a number of aposematic taxa (Alice Exnerová and Pavel Štys, personal communication) may lead to a conclusion that generalization occurs to a higher degree in the tropics than previously thought. An empirical finding that any latitudinal behavioral differences in generalization behavior exist would be illuminating in discussions of biogeographic patterns of diversity (see also Ricklefs 2009).…”
Section: Figurementioning
confidence: 94%
See 1 more Smart Citation
“…; Richards‐Zawacki et al . ) and are also used by females to distinguish local males, which are preferred (Maan & Cummings ). Similarly, some warning signals in lepidopterans are jointly involved with mate choice (Nokelainen et al .…”
Section: Introductionmentioning
confidence: 99%
“…A number of species display remarkable intraspecific diversity in colourpattern [19][20][21][22] , although in most cases the source of divergent selection among populations is unclear [23][24][25][26][27] . In Ranitomeya imitator, intraspecific divergence in colour-pattern is associated with selection for Müllerian mimicry 28 , which led to the establishment of four distinct mimetic morphs of this species in central Peru 29 .…”
mentioning
confidence: 99%